An air-breathing enzymatic cathode with extended lifetime by continuous laccase supply. (September 2018) - Kipf, Elena; Sané, Sabine; Morse, Daniel; Messinger, Thorsten; Zengerle, Roland; Kerzenmacher, Sven
Highlights: Enzymatic cathode with continuous laccase supply leads to extended lifetime. Air-breathing cathode design obviates the need for energy-intensive aeration. Cost-effective use of unpurified laccase in crude culture supernatant. Abstract: We present a novel concept of an air-breathing enzymatic biofuel cell cathode combined with continuous supply of unpurified laccase-containing supernatant of the white-rot fungus Trametes versicolor for extended lifetime. The air-breathing cathode design obviates the need for energy-intensive active aeration. In a corresponding long-term experiment at a constant current density of 50 µA cm −2, we demonstrated an increased lifetime of 33 days (cathode potential above 0.430 V vs. SCE), independent of enzyme degradation. The obtained data suggest that theoretically a longer lifetime is feasible. However, further engineering efforts are required to prevent clogging and fouling of the supply tubes. These results represent an important step towards the realization of enzymatic biofuel cell cathodes with extended lifetime and enhanced performance.